2018
DOI: 10.1111/cxo.12631
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment morphology after laser iridotomy in primary angle closure suspects

Abstract: Laser peripheral iridotomy induces significant changes in the 3-D anterior segment morphology in primary angle closure suspect patients. The Scheimpflug-Placido disc topographer provides reproducible measurements of the iridocorneal angle and other parameters measured and hence, may become clinically useful for non-invasive detection of potentially occludable angles. Predictors of iridocorneal angle widening after iridotomy were older age and anterior chamber volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…In this study, 100 patients with PACS were observed. It was found that the anterior chamber angle was widened, the ACD was deepened, the IC was decreased and the distance between the iris and the ciliary body was significantly shortened after LPI in a Guangzhou population with PACS, which is consistent with previous research results ( 14 17 ). The angle opening distance was related to the baseline ACD, IT750, AOD750, and LV before LPI.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 100 patients with PACS were observed. It was found that the anterior chamber angle was widened, the ACD was deepened, the IC was decreased and the distance between the iris and the ciliary body was significantly shortened after LPI in a Guangzhou population with PACS, which is consistent with previous research results ( 14 17 ). The angle opening distance was related to the baseline ACD, IT750, AOD750, and LV before LPI.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike our study, they also included patients with primary angle closure (PAC), PAC glaucoma, acute angle closure glaucoma and iris plateau con guration. However, other two studies involving a similar patient group as our study found no signi cant change in ACD after LPI [7,8]. We thought that the discrepancy in results was related to the different methodology of these studies.…”
Section: Discussioncontrasting
confidence: 63%
“…[ 8 ] measured the anterior segment parameters following LPI in PACD using Pentacam (Oculus Pentacam, Wetzlar, Germany) and compared it to measurements using AS-OCT (Carl Zeiss Meditec) and demonstrated a significant change in ICA, which was comparable to both the imaging modalities. Mansoori and Balakrishna[ 13 ] demonstrated a similar change using a Scheimpflug-based device with good reproducibility.…”
Section: Discussionmentioning
confidence: 92%
“…Our study did not show a significant difference in HVID, HACD, CCT, and CV after LPI in PACD patients, which is expected and similar to previous reports. [ 13 , 19 ]…”
Section: Discussionmentioning
confidence: 99%